Jewish Community Holidays (Journal of the College of Languages (JCL), 2017)
Is a day or series of days celebrated by Jews for religious or worldly important event in Jewish history as an occasion in Hebrew is called Eid יום טוב good day or good or חג תענית celebrate the festival or celebration. Most of the Jewish holidays are of a religious nature, and there is a worldly character with festivals such as the Festival of Lights חג החנוכה the holiday of Purim and the holidays, although a religious appearance, but she celebration in mundane aspects of the history and traditions of the Jewish occasions. Mass over the holidays when Jews are those mentioned in the Bible in my Leviticus and Deuteronomy. And some holidays established by rabbis in the vicinity of the ancient period of Jewish history, and the modern holiday was established in the modern era.